2013
DOI: 10.1063/1.4801969
|View full text |Cite
|
Sign up to set email alerts
|

Polarization reversal induced by heating-cooling cycles in MgO doped lithium niobate crystals

Abstract: Polarization reversal during heating-cooling cycles was investigated in MgO doped lithium niobate (MgO:LN) crystal using piezoresponse force microscopy. The essential dependence of the domain structure evolution scenario on the maximal temperature in the cycle has been revealed experimentally. It has been shown that the heating of the engineered domain matrix from room temperature to 85 C leads to light size reduction of the isolated domains at the matrix edges, whereas the heating to 170 C leads to essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…It is known that a temperature change can cause domain back switching and domain wall motion in LiNbO 3 and LiTaO 3 . [34][35][36] The net pyroelectric field E pyr inside the crystal is the sum of the depolarizing field E dep caused by the spontaneous polarization P s and a screening field E scr…”
mentioning
confidence: 99%
“…It is known that a temperature change can cause domain back switching and domain wall motion in LiNbO 3 and LiTaO 3 . [34][35][36] The net pyroelectric field E pyr inside the crystal is the sum of the depolarizing field E dep caused by the spontaneous polarization P s and a screening field E scr…”
mentioning
confidence: 99%
“…Ferroelectric materials have spontaneous polarizations that can be reversed under the application of stress, thermal radiation, light illumination, or external voltages to the materials. The domain walls (DWs) that occur between two neighboring polarizations with different orientations may be conducting, although the ferroelectric materials themselves are generally insulating. In recent years, domain wall nanoelectronics, in which bipolar voltages are used to create or erase the DWs required for information storage, has seen rapid development .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied the thermal stability of domains in various ferroelectric materials, such as Rb-doped KTiOPO 4 [20], LiTaO 3 [21], Pb(Zr 0.4 Ti 0.6 )O 3 [22], and LiNbO 3 [23,24]. They reported that the ferroelectric domains would degrade, or even disappear, after heat treatment.…”
Section: Introductionmentioning
confidence: 99%